Efektivitas Mikroorganisme Lokal (Mol) Kulit Pisang DanBonggol Pisang Terhadap Pertumbuhan Tanaman Selada(Lactuca sativa L) Pada Media Hidroponik - Oktiningtiyas, Lina Yekti, Dra. Suparti, M. Si (2015)
The content contained on the banana weevil are calcium, phosphorus, carbohydrates, protein, iron, while the banana skin contain nitrogen, carbohydrates and others that are necessary plant. Weevil bananas and banana skin can be applied as a liquid fertilizer or MOL (Local Microorganisms). This study aims to determine the effectiveness of the banana weevil MOL and banana skin on the growth of lettuce plants with hydroponics media. This study uses quantitative methods experiment with completely randomized design (CRD) two factors: the type of MOL (Q0: plain water, Q1: banana weevil, Q2: banana skin) and the concentration of MOL (P1: Concentration 18%, Q2: 24% concentration , P3: concentration 30%) and 9 treatments and 3 replications. Analysis of the data used is two way anova at the level of 5% F, known concentrations of MOL no significant effect on growth (stem length, number of leaves, leaf width), while the types of MOL significantly to the growth of lettuce plants. To know the real difference between the treatments tested the Least Significant Difference Q1P2 is 2.16 cm, number of leaves Q2P2 is 2, and the leaves are Q1P2 width of 1.5 cm.